Identification of risk factors for elevated serum IgG4 levels in subjects in a large-scale health checkup cohort study - Tsuji, Yoshika; Koga, Tomohiro; Nonaka, Fumiaki; Nobusue, Kenichi; Kawashiri, Shin-ya; Yamanashi, Hirotomo; Maeda, Takahiro; Arima, Kazuhiko; Aoyagi, Kiyoshi; Takahashi, Meiko; Kawaguchi, Shuji; Matsuda, Fumihiko; et al. (Frontiers in Immunology, 2023)
To allow the identification of IgG4-related disease (IgG4-RD) from a subclinical phase as it is important to understand the risk of elevated serum IgG4 levels. We planned to evaluate serum IgG4 levels in the participants of the Nagasaki Islands Study (NaIS), a large-scale health checkup cohort study. This study included 3,240 individuals who participated in the NaIS between 2016 and 2018 and consented to participate in the study. Serum IgG4, IgG, and IgE levels and human leukocyte antigen (HLA) genotyping results of the NaIS subjects as well as lifestyle habits and peripheral blood test results were analyzed. The magnetic bead panel assay (MBA) and the standard nephelometry immunoassay (NIA) were used to measure serum IgG4 levels. The data were evaluated using multivariate analysis to identify habitual and genetic factors associated with elevated serum IgG4 levels. Serum IgG4 levels measured with the NIA and MBA showed a tight positive correlation between the two groups (correlation coefficient 0.942). The median age of the participants in the NaIS was 69 years [63–77]. The median serum IgG4 level was 30.2 mg/dL [IQR 12.5–59.8]. Overall, 1019 (32.1%) patients had a history of smoking. When the subjects were stratified into three groups based on the smoking intensity (pack-year), the serum IgG4 level was significantly higher among those with a higher smoking intensity. Accordingly, the multivariate analysis identified a significant relationship between smoking status and serum IgG4 elevation. In this study, smoking was identified as a habitual factor correlating positively with elevated serum IgG4 levels.